MODERN TRENDS IN CLINICAL PHARMACOLOGY AND DRUG THERAPY (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This thesis examines modern trends in clinical pharmacology and drug therapy, focusing on recent advances in pharmaceutical research, innovative treatment strategies, and the rational use of medications in clinical practice. The study highlights the importance of personalized medicine, drug safety, pharmacovigilance, and evidence-based pharmacotherapy in improving patient outcomes. Modern pharmacological approaches contribute significantly to the prevention, diagnosis, and treatment of various diseases while reducing adverse drug reactions and enhancing therapeutic effectiveness. The paper also discusses current challenges and future perspectives in clinical pharmacology and drug development.